The Legal Regulation of the International Monetary System and its Response to the Interests of the International Community - Mahafzah , Emran (Dirasat: Shari’a and Law Sciences, 2021)
This paper discusses a highly complex and sensitive topic, related to the international monetary system, and its legal basis. It deals with the gold standard that was formed through international commercial dealings, which was a dedication of customary rules in this aspect. Then it deals with the arrangements reached at the Bretton Woods conference that linked the dollar to gold, and its transformation in subsequent dealings to a system in which the dollar is more dominant, which is supposed to be covered by gold. However, after the United States announced the cessation of exchanging dollars for gold in 1971, it became clear that the United States had printed more than three times the value of the gold it has. It also resorted to solve its problem by declaring what was called the floating currency system, as a system described as the international monetary anarchy. This paper shows the economic and political crises that resulted from this procedure issued by the United States. It also shows the legal reality of this system, which is closer to chaos governed by the hegemony of the dollar. Moreover, it offers ideas to reproduce a fair and acceptable international monetary system..